Investigation of the Interface Parameters of Fiber-Reinforced Composite Materials. Issue 1 (January 2014) - Xie, Zhimin; Chai, Dongliang; Weng, Yanyan; Du, Haiwen
Design of the interfacial properties is a significant fundamental issue in the field of composite materials. Much attention has been paid to the improvement of the interface strength, while there has been a little work concerning the mechanical design of the interface for fiber-reinforced polymers (FRPs) in which the fiber is transversely isotropic thanks to its orientation feature. Based on the conception of neutral inclusion and imperfect interface conditions, the interface parameters are obtained for the FRPs by using Kolosov constant. We demonstrate the effect of the thermal residual stresses on the neutrality for FRPs in this paper. If the interface has the properties of design parameters without consideration of thermal stress, the presence of thermal residual stress/strain would break the neutrality in the cases of equal-biaxial tension and pure shear. In particular, the neutral fiber does not exist unless the thermal stress is eliminated in the equal-biaxial tension. In the case of uniaxial tension, the neutral fiber does not exist in absence of thermal stress, while the neutrality would become possible by properly controlling the thermal residual stress. Because the large thermal residual stress will result in the formation of cracks in matrix, a trade-off design is necessary between the neutrality and the initiation of matrix cracking.